Molecular Detection and Sequencing of Peste Des Petits Ruminants Virus of Saurashtra Region of Gujarat, India - Tajpara, Mahesh M.; Shah, Nalinkant M.; Javia, Bhaveshkumar B.; Barad, Dilipsinh B.; Ramani, Umed V.; Patel, Dharmesh R.; Kalaria, Vinay A. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was undertaken with the objective of molecular detection and sequencing of the Saurashtra region’s Peste Des Petits  Ruminants virus. A total of 119 clinical samples (40 nasal swabs, 20 conjunctiva swabs, 16 oral swabs, and 19 tissues from goats along  with 22 nasal swabs and 2 tissues of sheep lung and intestine) were tested by N gene & F gene-based primers. Out of 119 samples,  35 samples were positive for N gene primer, and 32 positives for F gene primer. The N gene-based sequence analysis of three PPRV  obtained from Bhavnagar, Amreli, and Rajkot belonged to lineage IV (Indian strains), and all three PPRV sequences showed 100 %  genetic identity with each other and 98-99 % genetic identity with PPRV strain of Mehsana (North Gujarat), Bhopal (Madhya Pradesh),  Pune (Maharashtra), Jhansi (Uttar Pradesh), and Sungri (vaccine strain)
Keywords: Molecular detection; Peste Des Petits Ruminants virus; (PPR virus); Sequencing; Saurashtra region; Gujarat